BCL2 overexpression: clinical implication and biological insights in acute myeloid leukemia - Zhou, Jing-dong (Diagn Pathol, 2019)
BACKGROUND: BCL2 protein inhibitor venetoclax (ABT-199) has been authorized by Food and Drug Administration for relapsed/refractory chronic lymphoid leukemia with 17p deletion. Although venetoclax/ABT-199 also caused cell death in acute myeloid leukemia (AML), whether it could be applied to clinical treatment needs further studies. Here, we revealed clinical implication of BCL2 overexpression in de novo adult AML, and may provide theoretical basis for targeted therapy using venetoclax. METHODS: BCL2 expression was analyzed in adult AML patients from public datasets The Cancer Genome Atlas (TCGA) and confirmed by another independent cohort from our own data. RESULTS: BCL2 expression showed up-regulated in AML patients among TCGA data and confirmed by our own data. BCL2 overexpression was correlated with FAB-M0/M1, whereas BCL2 under-expression was related to FAB-M5. However, BCL2 expression has no effect on overall survival (OS) and leukemia-free survival (LFS) of AML patients (determined in BCL2(low) and BCL2(high) groups). Interestingly, in the BCL2(low) group, patients undergoing autologous or allogeneic hematopoietic stem cell transplantation (auto/allo-HSCT) had significantly better OS and LFS compared with patients only received chemotherapy, whereas, no significant difference was found in OS and LFS between chemotherapy and auto/allo-HSCT patients in the BCL2(high) group. BCL2 expression was found positively correlated with HOX family gene, and negatively correlated with tumor suppressor microRNA such as miR-195, miR-497, and miR-193b. CONCLUSIONS: BCL2 overexpression identified specific FAB subtypes of AML, but it did not affect prognosis. Patients with BCL2 overexpression did not benefit from auto/allo-HSCT among whole-cohort-AML and cytogenetically normal AML. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13000-019-0841-1) contains supplementary material, which is available to authorized users.